UPAYA PENINGKATAN KAPASITAS USAHA MIKRO “NASI UDUK KAK UWIR“ MELALUI RE-BRANDING, RE-PACKING, DAN RE-PROMOTING - Abdul Rachman; Arie Haura; Karmila Firdaus; Muhammad Fadilah; Muhammad Khairurredha; Idha Azizah (Jurnal Abdi Insani, 2022)
Crisis conditions caused by Coronavirus Disease 2019 (Covid-19) which spread widely to the Tangerang area. Various policies to prevent the spread of COVID-19 actually have bad implications for various other sectors, especially in the economic sector. The Covid-19 pandemic has made everything that was originally done offline/offline now turns into an online/online system, including the business activities carried out by the UKM "Nasi Uduk Kak Uwir" in Binong Village, Tangerang Regency. This community service activity aims to assist business actors "Nasi Uduk Kak Uwir" in the context of re-branding, re-packing, and re-promoting in order to increase business attractiveness so that it becomes a leading micro-enterprise. The activity is carried out using the PAR (Participatory Action Research) method, which is a method that actively involves all relevant parties (stakeholders) in reviewing ongoing actions. Through this method, nasi uduk business actors take part in re-branding, re-packing, and re-promoting activities in increasing the attractiveness of nasi uduk. The result of this activity is an effort to realize a futuristic business branding image, innovative and creative product packaging and digitalization of the marketing of “Nasi Usuk Kak Uwir” in the form of Go-food, Grab-food, Google maps and Instagram as digital marketing media so that “Nasi Uduk Kak Uwir” can compete and develop significantly into a leading micro-enterprise. Digitalization of marketing is carried out to facilitate transactions between sellers and buyers without any time and place limits and to assist SMEs in marketing their products online.